EP 48. Effects of thalamic deep brain stimulation on spontaneous language production. Issue 9 (September 2016) - Ehlen, F.; Vonberg, I.; Kuehn, A.; Klostermann, F.
Abstract : Introduction: The thalamus is thought to contribute to language-related functions, but specifications of this notion remain vague. Objectives: An assessment of potential effects of thalamic deep brain stimulation (DBS) on spontaneous language may help to delineate respective functions. Patients and methods: For this purpose, we analysed spontaneous language samples from thirteen (six female/seven male) patients with essential tremor (ET) treated with DBS of the thalamic ventral intermediate nucleus (VIM) in their respective ON vs. OFF conditions. Samples were obtained from semi-structured interviews and examined on multidimensional linguistic levels. The main results were correlated with a more general score of cognitive function. Results: In the VIM-DBS ON condition, participants produced significantly less hypotactic sentences compared to the OFF condition. This reduction correlated with the variation of the general cognitive score. Further, active VIM-DBS led to a decreased use of words from the open class. In conclusion, VIM-DBS appears to induce the use of a simplified syntactic and lexical structure. The findings are discussed in relation to the proposed functions of the thalamus for language-related cognitive behavior.